Financial digital transformation practice of power enterprises based on RPA - Wenju QUAN (Dianxin kexue)
In the era of big data,characterized as an important part of the field of artificial intelligence application,RPA technology can free financial personnel from large number of repetitive tasks and help them to invest more energy into high value-added work such as analysis and decision-making.By introducing RPA,power enterprises could improve the efficiency of financial process as well as the accuracy of financial data.RPA would also provide management and economic benefits to power enterprises through standardizing business processes.Therefore,it is important to explore the role of RPA technology in financial digital transformation through the practical case.Mean-while,it is necessary for managers to realize and control the risk caused by RPA.